Model e-marketingu pro firmu SSK Třinec, a.s. - Klusová, Alena (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato práce je zaměřena na marketing, internet a zejména na spojení marketingu a internetu, tzv. elektronický marketing. V teoretické části je popsán marketing, formy elektronického marketingu a nejrozsáhlejší forma elektronického marketingu, což je webová prezentace. Praktická část je v prvé řadě věnována charakteristice společnosti S.S.K., a.s., dále analýze webové prezentace společnosti a návrhu nového webu společnosti.

The paper focuses on marketing, Internet and, predominantly, the connection of marketing and Internet, the so-called electronic marketing. The theoretical part deals with the issues of marketing, forms of electronic marketing and the most widespread form of electronic marketing, i.e. web presentation. The practical part is predominantly devoted to the characteristics of S.S.K., a. s., and, in addition, to the analysis of the company’s web site and the design of the its new website.
The model of the e-marketing for the company SSK Třinec, a.s.
Keywords: Marketing; marketingový mix; elektronický marketing; internet; web; www stránky.; Marketing; Marketing Mix; Electronic Marketing; Internet; Web; Website.